PENGARUH NILAI JUAL OBJEK PAJAK, LUAS KEPEMILIKAN TANAH, DAN HARGA PASAR TANAH TERHADAP NILAI GANTI RUGI TANAH PADA PELAKSANAAN PEMBANGUNAN MANADO OUTER RING ROAD III - Hesty ., Mansyur; Bobby Vian Jhon Polii; Charles Reijaaldo Ngangi (AGRI-SOSIOEKONOMI, 2019)
This study aims to 1) Analyze the effect of individually of the sale value of the tax object, land ownership area, and land market price on the value of land compensation in land acquisition development Manado outer Ring Road III (MORR III). 2) Analyze the effect jointly between the sale value of tax objects, land ownership area, and land market price on the value of land compensation in the procurement of land for the construction of MORR III. This research was conducted at the construction site (MORR III) from February to October 2019. This research used quantitative descriptive methods. The data collected was primary data and secondary data. Primary data were obtained directly through interviews with key informants namely the Land Procurement Committee for Implementation of MORR III. Secondary data were obtained from the North Sulawesi Land Agency and the Central Statistics Agency. Secondary data is related to Tax Object Selling Value (NJOP) data, Land Ownership Area, Respondents' Livelihoods and Land Compensation Value for the construction of MORR III. The sample selection was done purposevely with a sample of 60 recipients of land compensation. Data Analysis Techniques use 1) Regression Analysis, and 2) Multiple Regression Analysis. The results showed that (1) the Sales Value of Tax Objects or values that showed the average price obtained from a sale and purchase transaction that occurred naturally was positively correlated and significantly affected the value of land compensation determined by the appraisal. Each increased in the Tax Object Sales Value of Rp. 1,000 per m2 will increase the price of compensation by Rp. 540 per m2. The variable area of land ownership owned by the community receiving land compensation in the construction of MORR III has no significant effect on the value of land compensation. An increase in the area of land ownership owned by the people affected by land acquisition for the construction of MORR III only increased the value of land compensation obtained by Rp. 5,840 per m2. Land market price variables or prices that indicated the market value of land were positively correlated and have a significant effect on the value of land compensation determined by the appraisal. Land market price increased of Rp. 1000 per m2 increased the price of land compensation by Rp.1,137 per m2. (2) Variable sale value of tax object, area of land ownership, and land market price indicated 64.0% representation of variables that affected the value of land compensation and jointly have a positive effect on the value of land compensation received by the community land acquisition affected in the construction of MORR III. *eprm*